Linking natural resources, agriculture and human health: case studies from East Africa - Li Pun, H.H.; Baumgaertner, J.U.; Greiling, J.; Gopalan, H.; Jabbar, M.A.; Mares, V.; McDermott, John J.; Odiit, M.; Mohamed-Saleem, M.A. (2002)
Past attempts to alleviate the problems of poor farmers engaged in mixed-crop-livestock production have generally focussed on the design and diffusion of new technologies targeted on specific components of the agroecosystem. Unfortunately, such piece-meal efforts have had little impact in the developing world, including the East African highlands, the focus of this report. This report descibes recent experiences of two research centres with a global reach: the International Livestock Research Institute (ILRI) and the International Centre of Insect Physiology and Ecology (ICIPE). Both are currently conducting research in the East African highlands, based on holistic, participatory methods. Each centres strategy integrates activities intended to improve food security and nutrition, human and environmental health, asset building and farm income, through natural resource management (NRM) and higher crop and livestock productivit computer modelling is one of the research tools used to assess the potential impact of using better methods to manage soil nutrients, graze and feed animals, enhance livestock health and control tsetse flies and other vectors.